Enhancing Security and Efficiency through QR Integration with Hybrid AES-ECC Algorithm in Mobile Apps for Cardless Data Transactions - J. Hamad, Noor; A. Abdulhameed, Abbas; H. Ali, Mudhafar (Al-Iraqia Journal for Scientific Engineering Research, 2023)
To improve and facilitate transactions between customers and financial institutions, the utilization of Internet banking has been leveraged to deliver a heightened caliber of service characterized by heightened security and efficiency in contrast to traditional banking modalities. It is suggested in this research introduces an innovative security framework, designed to furnish a protected mechanism ensuring secure communication, authentication, confidentiality, and safeguarding of financial transactions between banking institutions and end-users, all without necessitating reliance on a physical card. The fundamental underpinning of this proposed system involves the amalgamation of a Quick Response (QR) code with a hybridized Advanced Encryption Standard-Elliptic Curve Cryptography (AES-ECC) model. Following the successful installation of the security application on the mobile device, and subsequent to an accomplished registration and encryption of data inputs, encoding and decoding processes are facilitated through the intrinsic encoding and decryption keys embedded within this hybrid algorithm. The clientele receives a QR code containing encrypted transaction details, and upon scanning this code via the designated Android application, the pertinent information is promptly displayed. Empirical assessments validate the effectiveness of the suggested approach, demonstrating superior outcomes when juxtaposed with prevailing methodologies.